Impact of board diversity and audit on firm performance - Aqil Waqar Khan; Qazi Abdul Subhan (Cogent Business & Management, 2019)
The study investigates impact of board diversity and quality audit on financial performance by analyzing listed firms in Pakistan. Board diversity is investigated in terms of nationality diversity and gender diversity. Audit is studied in domain of quality audit and audit cost. Although various organizations want to have diverse board structure but still the implication of board diversity in firm performance is uncertain. Here in this study results illustrated an interesting depiction of board diversity and firm financial performance. Higher audit cost leads to more efficient audit services as compare to companies having less audit cost. The study sample comprises of listed companies in Pakistan Stock Exchange (PSE) 100 Index. PSE-100 index is selected on the basis of sector representation and highest market capitalization. Panel data set is collected with time span from 2008 to 2017. In methodology, the study utilized quantitative techniques from econometrics on panel data to fill the research gap in the existing governance literature. Findings suggest that presence of female board members contributed to enhance firm performance while number of female board members in board of director is not related to firm financial performance. Nationality diversity is negatively associated with firm financial performance mostly due to difference in cross-cultural perceptions and communication barriers. High audit cost indicates a good quality audit, due to the fact that extended audit hours and expert audit staff conduct more comprehensive investigation, which cost higher audit fees.
Keywords: 650; nationality diversity; female board members; audit cost; firm performance (ROA; ROE)